Code girls : the true story of the American women who secretly broke codes in World War II - Calkhoven, Laurie (Little, Brown and Company, 2019)
Draws on recently declassified documents to uncover the true story of American women who served the U.S. Army and Navy as code breakers during World War II. Describes how tens of thousands of women were recruited by the U.S. military to work as cryptographers, and how their contributions helped save lives and end the war.